Pengembangan Profesionalisme Guru Pai Dalam Menyongsong Era Society 5.0 Di Min Gunung Maddah Sampang - Habsoh . (CV. ITTC INDONESIA, 2025)
This study focuses on the professionalism of teachers and the development of teacher professionalism in anticipation of the Society 5.0 era at MIN Gunung Maddah, Sampang. It is based on the background of the education sector in the context of the era of society 5.0.The study has two research questions, which aim to identify the professionalism of PAI teachers in preparing for the society 5.0 era at MIN Gunung Maddah Sampang. The second aims to identify the efforts of the head teacher in developing the professionalism of PAI teachers in the era of society 5.0 at MIN Gunung Maddah Sampang. The research method used in this study is qualitative descriptive. The type is field research. Data is collected through interviews, observations, and documentation. The analysis technique is data condensation, data display, and drawing conclusions